A rapid functional decline type of amyotrophic lateral sclerosis is linked to low expression of TTN. Issue 8 (8th January 2016) - Watanabe, Hazuki; Atsuta, Naoki; Hirakawa, Akihiro; Nakamura, Ryoichi; Nakatochi, Masahiro; Ishigaki, Shinsuke; Iida, Aritoshi; Ikegawa, Shiro; Kubo, Michiaki; Yokoi, Daichi; Watanabe, Hirohisa; Ito, Mizuki; et al.
Abstract : Objective: To classify the patterns of functional decline in patients with sporadic amyotrophic lateral sclerosis (ALS) and explore the genetic backgrounds that modified these patterns. Methods: We included 465 patients with sporadic ALS in the analysis and clustered the longitudinal functional scores in the registered patients, using a mixture approach of a non-linear mixed-effects model. We conducted a genome-wide analysis of 572 983 single nucleotide polymorphisms (SNPs). We then assessed the association between the clusters of longitudinal functional scores and SNPs. Results: We identified the following four clusters of longitudinal functional decline in the cases: a rapid decline cluster, an intermediate decline cluster, a sigmoidal decline cluster and a moderate decline cluster. We identified seven SNPs associated with the rapid decline cluster, using a recessive model (p=3.47–8.34×10 −8 ). The OR for the probabilities of the rapid decline cluster ranged from 5.5 to 5.84. Homozygosity for the minor alleles in the seven SNPs, which constituted a linkage disequilibrium (LD) block, was associated with decreased expression of TTN (encoding Titin, a large sarcomere protein) in the expression quantitative trait loci database of a large-scale Japanese genetic variation database (p=8.6×10 −10 –1.1×10 −7 ). TTN expression in immortalised lymphocyte lines was decreased in patients who were homozygous for the minor alleles compared with those who were homozygous for the major alleles (n=19 in each group, p=0.002). Conclusions: We detected an LD block associated with a rapid functional decline in patients with sporadic ALS, which is linked to decreased expression of TTN .